Faktor yang Mempengaruhi Kinerja Sistem Informasi Akuntansi Pada Bank Perkreditan Rakyat di Kota Denpasar - Saraswati, Ida Ayu Setya; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi; Vol 34 No 10 (2024), 2024)
This research aims to show empirically how personal ability, motivation, top management support impact the performance of accounting information systems in BPR. The research population is all BPR employees in Denpasar City who operating accounting information systems. The purposive sampling method was used for sampling. This study had 63 respondents. Multiple linear regression analysis was used to analyze the data. The research results show that personal ability, motivation, top management support influence the performance of accounting information systems. The theories used are the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB).